2014
DOI: 10.1111/imm.12330
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of regulatory T cells and T helper type 17 cells in patients with chronic hepatitis C

Abstract: SummaryPegylated interferon and ribavirin combination therapy is known to be effective in suppressing viral replication in 50-60% of hepatitis C virus (HCV) -infected patients. However, HCV-infected patients often exhibit varied responses to therapy. Therefore, the identification of immunological markers associated with the clinical outcomes of antiviral treatment is critical for improvement of therapeutic options. In this study, we aimed to investigate the ratio of CD4 + CD25 + FoxP3 + regulatory T (Treg) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
7
27
0
Order By: Relevance
“…Although we did fi nd that HCV infection was accompanied by an increase in IL-17 levels, no association was found with viral load, in accordance with other authors [13,20]. Similarly, although IL-17 was also increased in alcoholics, we also failed to fi nd any association with daily ethanol intake or duration of alcoholism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although we did fi nd that HCV infection was accompanied by an increase in IL-17 levels, no association was found with viral load, in accordance with other authors [13,20]. Similarly, although IL-17 was also increased in alcoholics, we also failed to fi nd any association with daily ethanol intake or duration of alcoholism.…”
Section: Discussionsupporting
confidence: 89%
“…Hao, et al, also failed to fi nd differences between controls and 114 HCV -infected patients [20]. Therefore, a great deal of controversy exists regarding the role of Th17 cells in HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another group could not detect any change in Treg frequency or suppressive function at 8 or 24 weeks of therapy, or at 24 weeks at follow-up [56]. Wang et al could even observe a decline in Treg frequency, as identified as CD4+ CD25+ CD127low, at 9 months of therapy [57], a finding confirmed by Hao et al, who detected a drop in Treg proportions, estimated as CD4+ CD25+ FOXP3+, in rapid virological responder patients from 4 to 48 weeks of therapy [58]. In line with the latter studies, and with data in the mouse model of chronic LCMV infection [24], we have recently observed that Treg frequency significantly drops in the peripheral blood of CHC patients as early as at day 2 of IFN therapy, mostly in responder patients, suggesting that IFNs may acutely lead to a Treg decline which may be involved in the mounting of appropriate anti-viral responses (S.P., I.P., E.T., V.B.…”
Section: Ifn Therapy and Treg In Ms Chc And Cancermentioning
confidence: 84%
“…IL-17A has been implicated in the host defense against microbial pathogens but is also associated with inflammatory disorders when produced in excess [30,41], and the cytokine levels were correlated with serum ALT levels or viral copy numbers in CHC patients [21,42]. However, IL-17A was not significantly elevated in CHC patients when compared to the healthy control group in other studies [28,43]. We observed significant elevation of IL-17A levels only in non-RVR patients infected with HCV genotype 1 (Fig 1).…”
Section: Discussionmentioning
confidence: 96%